Stock indices and ratings in the securities market - Wan Qin (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of the research is the stock market, focusing on the mechanisms and frameworks underlying the functioning of stock indices and the assignment of stock ratings. The subject of the research is the interrelation and impact of stock indices and stock ratings on market dynamics, investment behaviour, and financial risk management strategies. The purpose of the master's thesis is to analyse the role of stock indices and stock ratings in modern financial markets, evaluate their influence on investment decision-making, and develop methodological approaches for using these tools to enhance portfolio management and risk assessment. Based on the results of the research, the author shows that investment stock index can achieve wealth appreciation, but the choice is different, the gains and losses are also different.
Фондові індекси та рейтинги на ринку цінних паперів
Scientific adviser: Oriekhova Kateryna, PhD in economics, associate professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Economics; stock index; stock rating; evaluation; performance; investment; risk; transparency; stability; regulation